CUSTOMER VALUE CREATION IN THE GENERICS PHARMACEUTICAL MARKET - Santos, Roberta (2010)
This paper integrates a wider case study on PharmCo, a pharmaceutical company that is currently building a strategy to entry the hospital generics market. The research aims to investigate what United Kingdom (UK) hospitals key decision makers perceive as value when purchasing generic pharmaceuticals, and how the company can co-create value with these customers. The outcome provides a customer value analysis model and value propositions recommendations so PharmCo can achieve competitive advantage in the market.